Thiocolchicoside Niosomal Gel Formulation for the Pain Management of Rheumatoid Arthritis through Topical Drug Delivery - Paradkar, Mansi; Vaghela, Sneha (Drug Delivery Letters, 2018)
Background & Objectives: About 1.5 million people in the world suffer from Rheumatoid Arthritis (RA). Nearly three times as many women have the disease as men. Methods: Topical Thiocolchicoside Niosomal gel was formulated by thin film hydration method using molar ratio of Span 60: Cholesterol (X1), hydration volume (X2) and sonication time (X3) as independent variables and vesicle size (Y1) and entrapment efficiency (%EE)(Y2) as dependent variables. Results: 23 full factorial design was used and T3 batch was optimized which showed 80.5%EE, 244.3nm vesicle size and -34.4mV zeta potential indicating its stability. % In-vitro drug release study showed 93.12% drug release after 24hrs and was stable in refrigerated condition over 30 days. Preliminary batches of Niosomal gel were formulated by using different concentrations of Carbopol940 and HPMCK4M and from evaluation of gelling temperature and gelling time, C3batch was selected for the preparation of Niosomal gel which was formulated using optimized batch of niosomes and it exhibited pH 6-7, 85.55% CDR, pseudo plastic rheological behavior with good gel strength indicating the sustained release of drug and suitability of the formulation. Conclusion: Thus, thiocolchicoside niosomal gel might prove as promising drug carriers for pain management of RA through controlled drug release and increased topical retention time so to improve patient compliance with reduced dosing frequency and side effects.
Keywords: thin film hydration method